2007
DOI: 10.1007/s00256-007-0386-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of phalanx bone three-dimensional surface segmentation from computed tomography images using laser scanning

Abstract: This study showed that manual segmentation of high-contrast, coronal, reformatted, CT datasets can accurately represent the true surface geometry of bones. Additionally, smoothing techniques did not significantly alter the surface representations. This validation technique should be extended to other bones, image segmentation and spatial filtering techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…The bony edges were outlined and used to reconstruct the 3D models of the femur and tibia. The accuracy of the 3D models was estimated at 0.4 mm according to the imaging resolution (DeVries et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…The bony edges were outlined and used to reconstruct the 3D models of the femur and tibia. The accuracy of the 3D models was estimated at 0.4 mm according to the imaging resolution (DeVries et al, 2008). …”
Section: Methodsmentioning
confidence: 99%
“…The relative overlap computed between the two raters was 0.89 for all the bones. The individual bones, the proximal, middle, and distal phalanges, had relative overlaps of 0.91, 0.90, and 0.87, respectively (19). …”
Section: Methodsmentioning
confidence: 99%
“…The process of delineating the anatomic structures can be performed via a variety of techniques including manual, semi-automated, and fully automated techniques. The ability to define geometrically accurate representations of bony structures has previously been studied by DeVries et al[21] While defining the phalanx bones of the hand, good agreement was found between manual raters (Jaccard metric = 0.91) and physical laser scans of the same specimens (surface distance = 0.20mm). To facilitate the creation of the anatomic models both semi-automated techniques such as the expectation-maximization algorithms [16] as well as artificial neural networks (ANNs)[17] have been explored.…”
Section: Surgical Simulation Techniquesmentioning
confidence: 99%